Effect of the combination of crude extracts of Penicillium griseofulvum and Fusarium graminearum containing patulin and zearalenone on rumen microbial fermentation and on their metabolism in continuous culture fermenters - Riccio, Maria Belen (2014)
Six single-flow continuous cultures were used to study the effects of the mycotoxins patulin (PAT) and zearalenone (ZEN) alone or in combination on rumen microbial fermentation. In each of the four 7-d periods, the fermenters were supplemented in a 2 × 3 factorial arrangement with two levels of PAT (0 and 20 mg/l) and three levels of ZEN (0, 5 and 10 mg/l). The treatments did not affect the apparent and true digestibility of organic matter. PAT alone decreased the digestibility of neutral detergent fibre (NDF) and acid detergent fibre (ADF) (p < 0.01), but in the presence of 5 or 10 mg/l of ZEN, there were no effects of PAT. In contrast, the digestibility of NDF and ADF was decreased at 10 mg/l of ZEN in the absence of PAT (p < 0.05). The pH of the fermenters increased after 2 and 3 d of PAT treatment (p < 0.01). PAT decreased the concentration of total volatile acids (VFA), the molar proportion of acetate and the acetate:proportionate ratio (p < 0.01). The molar concentrations of other VFA were unchanged. Ammonia N (NH3-N) flow increased (p < 0.05) and there was a tendency to a higher NH3-N concentration (p < 0.1) in fermenters with PAT. Total N, non-ammonia N and bacterial N as well as efficiency of microbial protein synthesis and efficiency of N utilisation were not affected by treatments. PAT was nearly completely degraded during incubation. The mean recovery of ZEN, α-zearalenol and β-zearalenol expressed as a proportion of administered ZEN was less than 50% in effluents from fermenters receiving only ZEN and ZEN plus PAT, respectively. With exception of fibre digestion, the co-administration of PAT and ZEN did not elicit interaction effects on most measured parameters of rumen metabolism.